Pengaruh Motivasi Dan Kondisi Keuangan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Dengan Kesadaran Sebagai Variabel Intervening Di Kalurahan Wukirsari - Sri Lestari Yuli Prastyatini; Ananda Olivia Rosalina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine: 1) The effect of motivation on motor vehicle tax compliance in the Wukirsari sub-district, 2) The effect of financial conditions on motor vehicle tax compliance in the Wukirsari sub-district, 3) The effect of motivation on motor vehicle taxpayer compliance through awareness as a variable intervening in the Wukirsari Village, 4) The effect of financial condition on taxpayer compliance through taxpayer awareness as an intervening variable in the Wukirsari Village, 5) the effect of tax awareness on motor vehicle taxpayer compliance in the Wukirsari Village.The motorized vehicle taxpayers in Wukirsari Village are the subject of this study's sample. Accidental sampling is the sampling technique employed. An online questionnaire was used to collect the data (google form). The number of questionnaires processed was 100 questionnaires, which could not be processed were 4 questionnaires and which could be processed were 96 questionnaires. Methods of data analysis using path analysis techniques (Path Analysis) with the help of the SPSS program. The findings revealed that: 1) Motivation has no positive effect on Motor Vehicle Taxpayer Compliance in the Wukirsari Subdistrict, 2) Financial Condition has a positive effect on Motor Vehicle Taxpayer Compliance in the Wukirsari Subdistrict, 3) Awareness does not mediate the influence of Motivation on Motor Vehicle Taxpayer Compliance in Wukirsari Village, 4) Awareness does not mediate the influence of Financial Conditions on Motor Vehicle Taxpayer Compliance in Wukirsari Village, 5) Awareness has a positive effect on Motor Vehicle Taxpayer Compliance in Wukirsari Village. Keywords: Financial Condition, Motivation, Taxpayer Compliance and Awareness